The Influence of Big Five Personality on Impulse Buying Behavior in Online Shopping - Zacky Ahmed; Andi Syakhrul Ramadhan; Christian Haposan Pangaribuan (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
The convenience of doing business in the modern period has changed many things, including the ease of purchasing and selling. By connecting impulsive online shopping behavior with the big five personalities, we aim to discover the truth about it. Responses from 94 young online users in various areas of Jakarta were evaluated using structural equation modeling. We used a random sampling method, and the variables were evaluated using a 5-point Likert scale. The present study discovered that the big-five personality traits are not as strongly associated with online impulsive buying: conscientiousness and neuroticism were a stronger driver of online impulse buying, while extraversion, agreeableness, and openness to experience were statistically insignificant.